Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review: 2

Answer

x=4

Work Step by Step

$\frac{4}{x-2}-\frac{x}{x+2}=\frac{16}{x^{2}-4}$ $\frac{4(x+2)}{(x-2)(x+2)}-\frac{x(x-2)}{(x-2)(x+2)}=\frac{16}{(x-2)(x+2)}$ $4x+8-x^{2}+2x=16$ $x^{2}-6x+8=0$ $(x-4)(x+2)=0$ x=4 or x=-2 Substitute x=-2 to the original formula and find that $\frac{x}{(-2)+2}$, $\frac{16}{(-2)^2-4}$, the denominator is 0, which is incorrect. So the answer is x=4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.